COVID‐19 in recent heart transplant recipients: Clinicopathologic features and early outcomes. Issue 5 (8th July 2020) - Lima, Brian; Gibson, Gregory T.; Vullaganti, Sirish; Malhame, Kathryn; Maybaum, Simon; Hussain, Syed T.; Shah, Samit; Majure, David T.; Wallach, Fran; Jang, Kristine; Bijol, Vanesa; Esposito, Michael J.; et al.
Abstract: Background: The impact of COVID‐19 on heart transplant (HTx) recipients remains unclear, particularly in the early post‐transplant period. Methods: We share novel insights from our experience in five HTx patients with COVID‐19 (three within 2 months post‐transplant) from our institution at the epicenter of the pandemic. Results: All five exhibited moderate (requiring hospitalization, n = 3) or severe (requiring ICU and/or mechanical ventilation, n = 2) illness. Both cases with severe illness were transplanted approximately 6 weeks before presentation and acquired COVID‐19 through community spread. All five patients were on immunosuppressive therapy with mycophenolate mofetil (MMF) and tacrolimus, and three that were transplanted within the prior 2 months were additionally on prednisone. The two cases with severe illness had profound lymphopenia with markedly elevated C‐reactive protein, procalcitonin, and ferritin. All had bilateral ground‐glass opacities on chest imaging. MMF was discontinued in all five, and both severe cases received convalescent plasma. All three recent transplants underwent routine endomyocardial biopsies, revealing mild (n = 1) or no acute cellular rejection (n = 2), and no visible viral particles on electron microscopy. Within 30 days of admission, the two cases with severe illness remain hospitalized but have clinically improved, while the other three have been discharged. Conclusions: COVID‐19 appears to negatively impact outcomes early after heart transplantation.